Virtual Reality: Characteristics and application in anxiety disorders and other clinical settings - Trotta, Nicoletta; Leccese, Adriana; Fiore, Pietro; Meyerbröker, Katharina (Rivista di Psicologia Clinica - Open Access, 2024)
Virtual Reality (VR) technology places users in a computer-generated three-dimensional environment where they experience a variety of visual and auditory cues related to their clinical needs. Despite the considerable growth of scientific knowledge in this field, the application of this knowledge to clinical practice has been slow. The purpose of this paper is to synthesize the evidence related to the application of VRET interventions in the treatment of various disorders such as eating disorders, or even psychotic disorders and addictions, dwelling on anxiety disorders, in adults and in developmental age. VR technologies make it possible to create and replicate dangerous and impossible situations in the real world by allowing the precise acquisition of data, facilitating a more careful evaluation of rehabilitation progress; moreover, by exploiting the features of immersiveness and presence, it is possible to virtually recreate the perfect clinical setting for each intervention.